2011
DOI: 10.1158/1940-6207.capr-10-0292
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prostate Cancer Risk Loci with Disease Aggressiveness and Prostate Cancer–Specific Mortality

Abstract: Genome-wide association studies have detected more than 30 inherited prostate cancer risk variants. While clearly associated with risk, their relationship with clinical outcome, particularly prostate cancer–specific mortality, is less well known. We investigated whether the risk variants are associated with various measures of disease aggressiveness and prostate cancer–specific mortality. In a cohort of 3,945 men of European ancestry with prostate cancer, we genotyped 36 single nucleotide polymorphisms (SNP): … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
4
40
2
Order By: Relevance
“…Nevertheless, in Pomerantz and colleagues’ study including the largest number (580) of PCa-specific deaths (7), the variant allele (A) at rs2735839 was significantly associated with PCa-specific mortality, consistent with our observation that the variant allele was associated with aggressive diseases, supporting the prognostic value of this SNP.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Nevertheless, in Pomerantz and colleagues’ study including the largest number (580) of PCa-specific deaths (7), the variant allele (A) at rs2735839 was significantly associated with PCa-specific mortality, consistent with our observation that the variant allele was associated with aggressive diseases, supporting the prognostic value of this SNP.…”
Section: Discussionsupporting
confidence: 87%
“…It was reported that this SNP, located at 19q13, was associated with GS (6, 7) and disease aggressiveness (6, 7, 29). We also observed that the variant allele (A) at rs2735839 was associated with more aggressive disease in patients with clinically localized PCa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 4030 such genes were identified. A second literature search of GWA studies of prostate cancer was conducted through the electronic database PubMed [214, 18, 4043] covering a total of ~40000 prostate cancer cases, identifying more than 70 susceptible SNPs that were reported to have significant association with prostate cancer. 35 SNPs were selected and summarized in Supplementary Tables S2 and S3 for eQTL analysis.…”
Section: Resultsmentioning
confidence: 99%